PROSES BERPIKIR REFLEKTIF SISWA SMA DALAM PEMECAHAN MASALAH PADA MATERI TURUNAN FUNGSI DITINJAU DARI EFIKASI DIRI (Studi Kasus pada Siswa Kelas XI IPA SMA Negeri Punung) - Genarsih, Tunjung; Kusmayadi, Tri Atmojo; Mardiyana, Mardiyana (Jurnal Pembelajaran Matematika, 2015)
Abstract: The purpose of this study is to describe the process of reflective thinking in solving the problem of high school students on the material terms of the derivative function viewed from self-efficacy. This research is classified in the qualitative descriptive study with the case study method. The subjects in this study were students of class XI IPA SMAN I Punung Pacitan in the second semester of academic year 2014/2015. The determination of the subject is by using purposive sampling, which is based on high, medium, and low self-efficacy. The research data taken from the test results of student worksÂ  and interviews ofÂ  students. Test of the credibility of the data is done by time triangulation. The data analysis technique is qualitative descriptive by Miles and Huberman. The results showed that (1) students with high self-efficacy using reflective thinking processes in a) stages of understanding the problem, able to select science, believing the truth, and actively create a consideration of the chosen solution; b) planning phase troubleshooting, make certain considerations, believing the truth, and select science; c) the stage of implementing the plan problem solving, able to explain the problem solving, linking information obtained by the problems encountered, deliberation, aware of the error and correct it, believing the truth; d) phase re-examine, re-examine, capable of linking the knowledge, correcting the error, explaining the final conclusion. (2) students with moderate self-efficacy use reflective thinking process in a) understand the problem, believing the truth, actively make judgments, and able to select science; b) the stage of implementing the plan problem solving, able to explain the solution of the problem, select the science that has been owned, believing the truth of solving the problem (3) students with low self-efficacy only use reflective thinking process in understanding the problem by being active characteristics in making judgments, be sure it is a correct problem-solving solutions.Keywords: reflective thinking, problem solving, mathematics, self-efficacy.